Mexican species of the genus Exenterus Hartig (Hymenoptera: Ichneumonidae: Tryphoninae) reared from diprionid hosts - Ruíz-Cancino, Enrique; Khalaim, Andrey I. (Zootaxa, 2015)
Two new species of the tryphonine genus Exenterus from Mexico, E. durangensis Khalaim & Ruíz-Cancino, sp. nov. and E. sehuerachicus Khalaim & Ruíz-Cancino, sp. nov., are described. Both species belong to the group of Exenterus species characterized by the unusually short, depressed tarsi. Exenterus durangensis was reared from the sawfly Zadiprion falsus Smith and E. sehuerachicus from Neodiprion autumnalis Smith (Hymenoptera: Diprionidae). This is the first record of the genus Exenterus as a parasitoid of these hosts. An identification key to separate the two Mexican species of Exenterus is provided.